Anomalously high rate refilling in the near lunar wake caused by the Earth's bow shock. Issue 9 (5th September 2017) - Xu, Xiaojun; Wong, Hon‐Cheng; Ma, Yonghui; Wang, Yi; Zuo, Pingbing; Zhou, Meng; Pang, Ye; Deng, Xiaohua
Abstract: On 28 July 2012, the Earth's bow shock crossed the lunar wake and was detected by the two ARTEMIS lunar orbiters in the solar wind and lunar wake, respectively. The bow shock and the Moon as well as the lunar wake have a very complicated interaction leading to some results that are very different from the ordinary bow shock and lunar wake. Our findings in this study include three main aspects. First, the bow shock has been deformed and thus collapsed as previously reported in the lunar wake. Second, ions and electrons with a density of up to 6.8 cm −3 refill in the near wake (<1 lunar radius from the lunar surface). The refilling electrons consist of two portions: drifting electrons and parallelly advecting electrons, while the refilling ions are all field aligned. Third, a current bifurcation within the shock ramp in the solar wind has been strengthened in relatively central part of the near wake. Our analysis strongly suggests that the bow shock has already been collapsed before it enters into the lunar wake caused by the interaction with the diamagnetic current system. Electrons with large pitch angles can be trapped in the strengthened bifurcation and taken into the near wake. However, both low‐energy electrons and ions can easily enter into the near wake, which is very different from ordinary lunar wake pattern. We infer that the drifting and trapped electrons may have played an important role in this event. Key Points: A case study of the Earth's bow shock passing through the lunar wake Ions and electrons with a density up to 6.8/cc refilling in the near lunar wake Evidence for the bow shock interaction with the lunar wake diamagnetic current